Media Framing of QS. al-Nisā’ [4]: 34 by @quranreview on Instagram: Glorifying Women Tendencies in Interpretation - Ghozali, Mahbub; Nurmadiansyah, Muhammad Toriq (Jurnal Studi Al-Qur’an, 2023)
This study examines @quranreview’s interpretation of Qur’anic verse QS. al-Nisā’ [4]: 34 on social media, focusing on the words used to convey meaning. Interpreting the Qur’an on social media is often simple and direct, as it involves exploring the meaning of verses through individual comments. However, this approach needs to improve in that it can sometimes overlook the central message of the verse due to its focus on individual words. Discovering the tendency of word choice in interpreting the Qur’an contributes to developing interpretation in social media. Through a qualitative analysis using critical discourse analysis by Teun A. van Dijk, we found that @quranreview deliberately chooses representative words to challenge the traditional interpretation of the verse, which can be discriminatory towards women. The study highlights the importance of careful word choice in interpreting the Qur’an on social media, especially when dealing with sensitive and controversial topics. It also suggests that @quranreview’s tendency to glorify women in its interpretation can contribute to a broader and more nuanced understanding of the text.